Detection and analysis of metal impairment inside wall using UWB modified antipodal vivaldi antenna - Shaikh, Faraz Ahmed; Khan, Sheroz; Zaharudin, Zarimin; Alam, Zahirul; Abdul Rahman, Farah Diyana; Badron, Khairayu; Yaacob, Mashkuri; Shahid, Zeeshan; Shaikh, Humaiz; Ahmed, Syed Faiz (IEEE, 2018)
This paper present a detection technique of metal placed inside and between two walls. A unique scheme of recognition of metallic objects through Ultra Wide Band (UWB) Modified Antipodal Vivaldi Antenna (MAVA) frequency range of (3.1GHz to 10.6 GHz) is presented in this paper. The working mechanism of detection system based on Time Domain Reflectrometry (TDR) using through wall imaging (TWMI). A very small duration pulses generated by Vector Network Analyzer (VNA) which are used for illuminating the wall. The investigation of outcomes of a system under UWB antenna probe array. The simulation results of MAVAhave given a massive potential of penetration, in order to identify concealed metal objects with fine accuracy, proving a smart development in the detection system technology. The improvement of resolution in an image, special filters have been developed and implemented. The design and optimization progression is conceded out via CST simulation software for parametric performance assessment of return loss, radiation pattern and directivity.